Design and evaluation of a dynamic knee-ankle-foot orthosis - Yakimovich, Terris (University of Ottawa (Canada), 2005)
Conventional knee-ankle-foot orthoses (KAFOs) or leg braces lock the knee in full extension and therefore do not permit a natural gait pattern. A new electro-mechanical dynamic knee-ankle-foot orthosis (DKAFO) that incorporates a new dynamic knee joint (DKJ) was designed to provide a more natural gait for people with knee extensor muscle weakness. The DKAFO inhibits knee flexion while allowing knee extension during weight bearing. During swing or other non-weight bearing activities, the DKAFO allows free knee motion. A prototype knee joint was mechanically tested to determine the moment at failure, loading behaviour, and device safety. Quantitative kinematic gait analysis of three able-bodied subjects and three KAFO users showed that walking with the DKAFO had a minimal effect on normal gait. The DKAFO offered increased knee motion in swing and a reduction in gait abnormalities for some subjects with disabilities. Future efforts will be made to modify the design to increase the factor of safety, and reduce DKJ dimensions.
Keywords: Engineering, Biomedical.; Engineering, Mechanical.